2017
DOI: 10.1073/pnas.1705080114
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for lipid binding to apoE and the role of intrinsically disordered regions coupled to domain–domain interactions

Abstract: Relative to the apolipoprotein E (apoE) E3 allele of the APOE gene, apoE4 strongly increases the risk for the development of late-onset Alzheimer's disease. However, apoE4 differs from apoE3 by only a single amino acid at position 112, which is arginine in apoE4 and cysteine in apoE3. It remains unclear why apoE3 and apoE4 are functionally different. Described here is a proposal for understanding the functional differences between these two isoforms with respect to lipid binding. A mechanism is proposed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
104
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 60 publications
7
104
0
9
Order By: Relevance
“…Since the N-and the C-terminal domains are connected by a long intrinsically disordered region (IDR), it is possible that Ab intercalates at the interface of the domains disrupting the native salt bridges and hydrophobic interactions. Furthermore, the disordered hinge domain may allow rotation of the C-terminal domain generating more than one interfaces as proposed by Frieden et al [50]. A recent computational study using docking and molecular dynamics simulations has shown that Ab can replace the native salt bridges and disrupt the structure of the N-terminal domain of apoE [33].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the N-and the C-terminal domains are connected by a long intrinsically disordered region (IDR), it is possible that Ab intercalates at the interface of the domains disrupting the native salt bridges and hydrophobic interactions. Furthermore, the disordered hinge domain may allow rotation of the C-terminal domain generating more than one interfaces as proposed by Frieden et al [50]. A recent computational study using docking and molecular dynamics simulations has shown that Ab can replace the native salt bridges and disrupt the structure of the N-terminal domain of apoE [33].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the disordered hinge domain may allow rotation of the C‐terminal domain generating more than one interfaces as proposed by Frieden et al . . A recent computational study using docking and molecular dynamics simulations has shown that Aβ can replace the native salt bridges and disrupt the structure of the N‐terminal domain of apoE .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report apoE4 is more susceptible to proteolysis compared to the other major isoforms of APOE [73,74], and other studies have demonstrated the presence of apoE4 fragments (14-20 kDa) in AD brains [75,76]. Structural differences between apoE3 and apoE4, particularly at the hinge region between the N-and C-terminal domains, may explain their different susceptibility to proteolytic degradation as well as lipid binding affinity [77]. In spite of these numerous observations, the exact nature of the protease responsible for apoE4 cleavage is unknown, although several candidates have been reported including cathepsin D [78], aspartic proteases [79], and a chymotrypsin-like protease [73].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that apoE contains intrinsically disordered regions and smaller flexible regions that surround structured helices, affecting the conformation and functional properties of apoE (14)(15)(16). Several biophysical studies have shown that apoE displays low thermodynamic stability and significant conformational plasticity, and allelic differences as well as single point mutations have been shown to affect protein conformation and to hinder physiological function (13,15,16,(18)(19)(20). Furthermore, apoE has been shown to be prone to aggregation and to form oligomeric structures in solution (21,22).…”
mentioning
confidence: 99%